Tooth loss and the risk of cognitive decline and dementia: A meta-analysis of cohort studies - Li, Liqing; Zhang, Qi; Yang, Di; Yang, Sule; Zhao, Yulan; Jiang, Min; Wang, Xiaofang; Zhao, Ling; Liu, Qi; Lu, Zuxun; Zhou, Xiaogang; Gan, Yong; et al. (Frontiers in Neurology, 2023)
Introduction Epidemiological studies have shown that tooth loss may be associated with an increased risk of cognitive decline and dementia. However, some results do not show a significant association. Therefore, we performed a meta-analysis to evaluate this association. Methods Relevant cohort studies were searched in PubMed, Embase, Web of Science (up to May 2022), and the reference lists of retrieved articles. The pooled relative risk (RR) and 95% confidence intervals were computed using a random-effects model (CI). Heterogeneity was evaluated using the I2 statistic. Publication bias was evaluated using the Begg's and Egger's tests. Results Eighteen cohort studies met the inclusion criteria. Original studies with 356,297 participants with an average follow-up of 8.6 years (ranging from 2 to 20 years) were included in this study. The pooled RRs of tooth loss on dementia and cognitive decline were 1.15 (95% CI: 1.10–1.20; P < 0.01, I2 = 67.4%) and 1.20 (95% CI: 1.14–1.26; P = 0.04, I2 = 42.3%), respectively. The results of the subgroup analysis showed an increased association between tooth loss and Alzheimer's disease (AD) (RR = 1.12, 95% CI: 1.02–1.23) and vascular dementia (VaD) (RR = 1.25, 95% CI: 1.06–1.47). The results of the subgroup analysis also showed that pooled RRs varied by geographic location, sex, use of dentures, number of teeth or edentulous status, dental assessment, and follow-up duration. None of the Begg's and Egger's tests or funnel plots showed evidence of publication bias. Discussion Tooth loss is associated with a significantly increased risk of cognitive decline and dementia, suggesting that adequate natural teeth are important for cognitive function in older adults. The likely mechanisms mostly suggested include nutrition, inflammation, and neural feedback, especially deficiency of several nutrients like vitamin D.